Contacts for silicon IMPATT and pick-off diodes - Boltovets, N.S.; Goncharuk, N.M.; Krivutsa, V.A.; Chaika, V.E.; Konakova, R.V.; Milenin, V.V.; Soloviev, E.A.; Tagaev, M.B.; Voitsikhovskyi, D.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2000)
We studied experimentally: (i) the ways to fabricate metal-n⁺-Si ohmic contacts with Schottky barriers; (ii) how elemental, structural and phase composition of barrier layers in the contact system, as well as of the barrier layer-semiconductor interface, depend on the formation techniques and conditions; (iii) their evolution at heating and under ⁶⁰Co g-radiation. Some versions of technique to form palladium, titanium, gold barrier layers using thermal and magnetron sputtering, as well as thermionic synthesis, are discussed. We investigated the structure, as well as phase and elemental composition, of both the barrier layers in contact system and barrier layer-semiconductor interface as a function of the formation techniques and conditions, and their evolution under heating and ⁶⁰Co g-radiation. For technological processes of contact system and mesa formation a simulation was performed to determine what contact systems are promising for use in manufacturing technology of silicon IMPATT and pick-off diodes for the millimeter wavelength range. Some conditions have been found that are necessary for production of high-performance contact systems. The heat and radiation tolerance ranges for barrier structures were considered. It was shown that the Si-Ti-TiB2-Au contact systems are best suited for production of silicon IMPATT and pick-off diode structures intended for the millimeter wavelength range.